PSYCHOLOGICAL READINESS OF THE FUTURE TEACHER TO COMMUNICATION WITH STUDENTS: THE MAIN TASKS - Sapozhnikov S (Alfred Nobel University Publisher, 2019)
The publication reveals the cause-effect relationships that are the basis of the psychological difficulties in communicating between future teachers and students and also substantiates the importance of using the method of active social psychological training (ASPT) for their professional training, reveals the peculiarities of functioning of "psychological defense", which has negative impact on pedagogical teaching skills of the future teacher. The article shows that the most important condition for pedagogical professionalism is not only the teachers' perfect knowledge of their subject but also such qualities as openness, goodwill, empathy, sincerity, ability to accept and understand others. To provide these personal preconditions for pedagogical professionalism, special training is required, which gives more than mastering academic knowledge and obtaining a set of recommendations. The article argues that the formation of the necessary personal qualities in the teacher is a very complex and emotionally rich process. It is noted that only by virtue of the actual emotional experience of the communication situation the future teacher can reach productive conclusions that will contribute to his or her personal development. The psycho-correction work presented in the article is ensured by the method of active social-psychological training (ASPT). Particular attention in the article is paid to the analysis of the integrity of the subject's psyche in the process of communication, as well as the discovery of unconscious contradictory components that define it as a contradiction. It is argued that helping a subject in the realization of discrepancy (conditioned by "protection") allows to make a transition into contradictions and thus contributes to personal development. It is noted that the way to this lies through the knowledge of human behavior since it expresses both conscious and unconscious phenomena, reveals the objective contradictions of the phenomena themselves, which are not yet realized. All of the above-mentioned is impossible to implement without scientific management of the process of personality development and timely disclosure of disproportionality, which is characterized by the presence of diverse motivational tendencies in order to help the individual in their awareness and constructive resolution.